Effect of boron on growth and flowering in gladiolus (Gladiolus sp.) (Current Horticulture, 2024)
A field trial was conducted to find out the optimum dose of Boron in maximizing growth and improving flowering attributes  in gladiolus (Gladiolus sp.) cv. Malaviya Shatabdi at Institute of Agricultural Sciences, Banaras Hindu University, Varanasi,  Uttar Pradesh during 2020-21. The treatments were given as: the control (distilled water), 0.1% boron, 0.2% boron, 0.3% boron,  0.4% boron, 0.5% boron, 0.6% boron, 0.7% boron, 0.8% boron, 0.9% boron and 1.0% boron, applied at 60 and 75 days after  planting. There was maximum number of leaves/plant (13.94), maximum width of scape (2.67 cm) was noted at 0.3% of B,  maximum plant height was recorded with foliar application of 0.5% B (70.42 cm), whereas leaf length (65.50 cm) and leaf width  (2.63 cm) were maximum at 0.6% of B as compared to other treatments. The earliest spike emergence and colour were noted  in 68.44 days and 77.88 days respectively at 0.2% of B spray. Earliest opening of first and fifth florets was seen with 0.6% of B  (85.06 and 90.00 days respectively). Maximum length (9.72 cm) and diameter (7.81cm) of first floret was observed in 0.2 % and  0.3% B treatments, whereas, maximum length (8.62 cm) and diameter (7.40 cm) of fifth floret was detected in 0.6% and 0.5%  B treatments respectively. Results also showed that application of B significantly reduced flowering duration among all the  treatments as compared to the control.
Keywords: Corms; Boric acid concentrations; Foliar spray; Vegetative and floral characters